Web-Based School Profile Information System for Enhancing Digital Promotion and Public Information Access at SDN 65 Jatibaru - Hesti Faradilla; Syarifuddin; Dahlan (Journal of Digital Technology and Computer Science, 2026)
Purpose – This study aims to design and evaluate a web-based school profile information system as a digital promotional medium for SDN 65 Jatibaru, Bima City. The system addresses the limitations of manual information dissemination and supports broader public access to school information. Methods – This study employed the Waterfall development model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using PHP and MySQL, supported by HTML5, CSS3, and JavaScript for a responsive user interface. Functionality was evaluated through Black Box Testing, while user acceptance was assessed using a User Acceptance Test questionnaire involving 26 respondents, consisting of 3 administrators/teachers and 23 visitors/parents. Findings – The system provides features for managing school profiles, teacher data, student data, student achievements, school programs, and photo galleries. Black Box Testing showed that all 32 test scenarios were successfully completed, resulting in a functional validity rate of 100%. User acceptance results showed feasibility scores of 94.0% from administrators/teachers and 90.2% from visitors/parents, both categorized as Very Feasible. Research Implications – The findings indicate that a PHP/MySQL-based school profile system can support digital promotion and public information access in primary schools. However, the lower information-completeness score among administrative users indicates the need for future improvement in content completeness and administrative usability. Originality – This study contributes a dual-perspective user acceptance evaluation involving internal school users and external public users, providing a more balanced assessment of system feasibility for school digital promotion.